The Protein Losses of Three Major Cereal Crops by Natural Disasters in China From 1988 to 2020 - Huang, Dongmei; Chen, Yifei; Chen, Pinghua; Zheng, Qingchang (Frontiers in Environmental Science, 2022)
Natural disasters have a major detrimental impact on agricultural production. In recent decades, China has experienced increasing natural disasters as a result of climate change. Although the spatial and temporal changes in natural disasters for individual catastrophe activities are well understood, the impact of several disasters on cereal crop productivity and subsequent quality loss remains unknown. Furthermore, due to the key significance of cereal in China's daily diet, the decrease of cereal quality, namely protein, will have a detrimental impact on nutrient supply. To close the gap between natural disasters and cereal crop food quality in China, we used province-level data from 1988 to 2020 to construct a dataset of natural disasters, crop production, and protein contents in cereal crops (rice, wheat, and maize). Our findings suggest that activities in affected areas of natural disasters have decreased dramatically since the 21st century, with changes in affected areas of natural disasters varying by province. Between 1988 and 2020, the total protein loss from grain and straw harvests due to natural disasters were 11.93 and 391.27 million tons, and drought was responsible for half of the protein loss in more than half of the provinces.